Japan through the lens of the Tokyo Olympics - Holthus, Barbara G.; Gagné, Isaac; Manzenreiter, Wolfram; Waldenberger, Franz 1961- (Routledge, 2020)
"This book situates the 2020 Tokyo Olympics within the social, economic and political challenges facing contemporary Japan. Using the 2020 Tokyo Olympics as a lens into the city and the country as a whole, the stellar line up of contributors offer hidden insights and new perspectives on the Games. These include city planning, cultural politics, financial issues, language use, security, education, volunteerism and construction work. The chapters then go on to explore the many stakeholders, institutions, citizens, interest groups, and protest groups involved, and feature the struggle over Tokyo's extreme summer heat, food standards, the implementation of diversity around disabilities, sexual minorities and technological innovations. Giving short glimpses into the new Olympic sports, this book also analyses the role of these sports in Japanese society. Japan Through the Lens of the Tokyo Olympics will be of huge interest to anyone attending the Olympic Games in Tokyo 2020. It will also be useful to students and scholars of the Olympics and the sociology of sport, as well as Japanese culture and society"-- Provided by publisher